2018
DOI: 10.1152/ajpheart.00252.2018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel microRNA profile in pediatric patients with cancer treated with anthracycline chemotherapy

Abstract: This study demonstrated for the first time that changes in miR expression occurs in pediatric AC patients. These findings suggest that miRs are a potential strategy for early identification of AC patients susceptible to LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…In our study of canine cancer patients receiving single agent DOX chemotherapy, selected EV‐miRNA were differentially expressed with DOX treatment: miR‐107 and miR‐146a were downregulated whereas miR‐502 was upregulated after just 2 doses of DOX. Our results are similar to those seen in human pediatric patients receiving single agent anthracycline treatment that showed downregulation of total serum miR‐107 1 year after completion of treatment, and downregulation of miR‐146a 24 to 48 hours after the initiating of DOX treatment 17 . Unlike the study of children, we did not find a correlation between these 2 miRNAs and LVEF, but our study utilized a much smaller sample size and may not have had sufficient statistical power to detect a correlation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study of canine cancer patients receiving single agent DOX chemotherapy, selected EV‐miRNA were differentially expressed with DOX treatment: miR‐107 and miR‐146a were downregulated whereas miR‐502 was upregulated after just 2 doses of DOX. Our results are similar to those seen in human pediatric patients receiving single agent anthracycline treatment that showed downregulation of total serum miR‐107 1 year after completion of treatment, and downregulation of miR‐146a 24 to 48 hours after the initiating of DOX treatment 17 . Unlike the study of children, we did not find a correlation between these 2 miRNAs and LVEF, but our study utilized a much smaller sample size and may not have had sufficient statistical power to detect a correlation.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, miRNAs can affect various aspects of cell metabolism, influencing processes such as differentiation, regeneration, and apoptosis, and therefore are implicated in disease pathogenesis, making them attractive as indicators of disease state. In addition, miRNAs are released by cells into biofluids, 15 where they are relatively stable and can withstand prolonged periods of storage even at room temperature 16,17 . Their stability is in part provided by membrane‐bound nanoscale entities called extracellular vesicles (EVs).…”
Section: Introductionmentioning
confidence: 99%
“…A striking feature of many, if not all, published papers is that no study described a decline of LVEF below the "normal" threshold of 50%, possibly because of lack of a long-term follow-up. Moreover, the vast majority of human-based research studies concentrated on the acute phase of cardiotoxicity 158 , and the same limitations often apply also to experimental researches, which rarely go beyond a few days' time span from treatment to sacrifice.…”
Section: Opportunities and Limitations In The Use Of Noncoding Rnas In Cardio-oncologymentioning
confidence: 99%
“…More than 1,900 human miRNAs have been annotated in the miRBase database (miRBase: MicroRNA, University of Manchester, Manchester, United Kingdom) and a number of miRNAs have already been shown to be associated with myocardial injury and cardiovascular death. Oatmen et al ( 14 ) compared serum miRNA profiles in anthracycline-treated pediatric patients with age-matched controls. Using a customized microarray of 84 miRNAs associated with cardiovascular diseases, the authors observed significantly altered miRNA expression with anthracyclines and identified 8 miRNAs that correlated with cardiotoxicity.…”
Section: Omics Approaches For Novel Biomarker Discoverymentioning
confidence: 99%